The necessity of considering the challenges facing Olympic Movement - Mohammadi, S.; Keyvan, A. D. (Journal of Human Sport & Exercise, 2011)
From the beginning that the modern Olympic Games formed, Coubertin had decide to establish and governance of amateurism in the Olympic Games. He always tried to keep Olympics Games far from issues such as professionalism in sport, issues and political tensions, seeking power of some countries, racism and political supremacy. So, by studying problems that threatens Olympic movement, can step important pace to identify the main objectives and Olympic ideals more accurately and give proper strategy to deal with these problems to withdraw its advance. In this present study we evaluate problems that threatening Olympic movement. The method used in this study is historical. So by using the documentary papers, magazines and internet, we evaluate the main problems of the Olympic movement with its details. Because the method used in this study is documentary and library-style, so it hasn't statistical population and sample. Also the research materials was articles, internet and thesis and etc. that has been done by studying sheets, classification, formulation and analyzing the data content. Finally we can say perhaps because of far away from the Olympic ideals, caused to today's threats. So by approach to those aims that was due to founders thought, Olympic movement would be saving.